Aspectos científicos, técnicos, éticos e legais do DNA forense - Millard, George Henry (2015)
The analysis of DNA for the purpose of obtaining genetic profile has become essential for criminal investigation and judicial procedure. Since the origins of the techniques of human identification, nothing has been discovered with greater discriminatory power, between two randomly chosen individuals. Genetic proof has assumed great importance in the courts, however, for the operators of law this whole theme is cloaked in great mystery. The objective of this study was to obtain, and to offer to the operators of Law, a general view on the utilization of genetic profiles, and their consequences for the system, and Brazilian society. However, this powerful tool of human identification, DNA and its interconnections, has been thrust forward by very recent advances, in such volume as to alter in a significant way procedures and results, being obliged to follow the paths beaten by scientists, for a simplified form to put into order the information which has directed the forensic genetics to it's current point in time. A review of human identification was made until the discovery of DNA, its structure, evolution and development. The procedures and the various techniques were analyzed, which were being perfected for the obtaining results from the collecting of biological traces at the crime scene to the laboratory analysis, culminating with automatization by PCR and the elaboration of a genetic profile. DNA in the Forensic world, it's birth and consecration were examined. The presence of the instruments available for working the markets, bestowing greater means of discrimination, the STR tests, the future of the SNPs, the sequence of the second generation, and the obtaining of phenotypic characteristics, were duly dealt with. It was analysed, since its origin and implantation up to the current time, the working of the more significant Genetic Profile Data Banks, its technical and legal concerns, as well as the situation in Brazil, with its advances and obstacles, to become part of the forensic DNA community. Experiments in the testing of carbonized human bones were carried out, for identification in criminal procedure, with full details of the materials utilized, methodology, laboratory equipment and software for analyzing the results, ending up with a conclusive result. Following on the exploratory part was carried out through visits to the most expressive world DNA centres, located in the USA, France, the United Kingdom and Brazil, aimed at by means of interviews to discuss this topic, from technical to ethical aspects, and of the data banks to the operations of the system. Finally, in the discussion, the points observed in the centres of excellence, the results of the interviews, and the possible advantages of each system, in a totally fractioned global posture, were addressed.